Unit-linked life insurances – a comparative analysis of the selected offers - Kałuska, Maria (Journal of Finance and Financial Law, 2022)
The purpose of the article/hypothesis: The main purpose of the article is to compare and evaluate the conditions of unit-linked life insurances offered by three selected insurance companies. The result of the analysis will allow to determine which of the compared insurance offers is the most beneficial for the policyholder. The following research hypothesis was formulated: the insurer specializing in the sale of unit-linked life insurance offers the potential policyholder the most beneficial terms in comparison to the majority of the analyzed insurance. Methodology: In the article the following methods were used: a review of unit-linked life insurance offers and a comparative analysis using indicators used to measure the risk level and efficiency of investment funds. Results of the research: Conducting a comparative analysis enabled to positively verify the research hypothesis. The Plan na Przyszłość+ insurance offered by Aegon Życie SA, the insurer whose majority of life insurance is unit-linked life insurance, is substantially the most beneficial. It is the most important advantages are the widest scope of insurance, the guarantee of the payment of a fixed sum insured, insignificant amount of fees, as well as a low level of risk and the highest efficiency of the investment fund associated with the insurance.